2013
DOI: 10.1159/000352011
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Working Memory via N-Back Task in Euthymic Bipolar I Disorder Patients: A Review of Functional Magnetic Resonance Imaging Studies

Abstract: Bipolar disorder (BD) is a chronic and highly disabling mood disorder, associated with the highest suicide rate among psychiatric disorders. Even though neurobiological bases of BD have still to be further elucidated, recent neuroimaging studies provided compelling evidence about functional correlates of cognitive deficits in BD patients, with working memory (WM) impairment being one of the most commonly reported findings. Such dysfunctions are likely to persist beyond acute phases of the illness, so they qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 103 publications
2
35
3
Order By: Relevance
“…Consistent with the literature (Cremaschi et al, 2013, McKenna et al, 2013, Thompson et al, 2007, Torres, Boudreau, 2007), we found that euthymic bipolar subjects performed worse on working memory tasks. Additionally, both working memory and processing speed domain scores were significantly associated with corpus callosum white matter integrity (FA values) in the entire sample (the correlation was driven mostly by the bipolar subjects).…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with the literature (Cremaschi et al, 2013, McKenna et al, 2013, Thompson et al, 2007, Torres, Boudreau, 2007), we found that euthymic bipolar subjects performed worse on working memory tasks. Additionally, both working memory and processing speed domain scores were significantly associated with corpus callosum white matter integrity (FA values) in the entire sample (the correlation was driven mostly by the bipolar subjects).…”
Section: Discussionsupporting
confidence: 92%
“…Neurobiological differences in brain activation during working memory tasks in bipolar I disorder may be trait characteristics and are thus present outside of depressive episodes. A recent review (Cremaschi et al 2013) of n-back fMRI studies of medicated euthymic subjects diagnosed with bipolar I disorder revealed altered activation and connectivity within the ventrolateral circuit and parieto-temporal circuit dysfunction rather than dorsolateral. Although we did not include euthymic subjects with bipolar II disorder in this study, it may be that bipolar II disorder is associated more with ventrolateral circuit rather than dorsolateral circuit dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Though there are two primary subtypes of bipolar disorder, investigations of the neuropathology of working memory impairments have focused on bipolar I disorder. For example, a recent meta-analysis (Cremaschi et al 2013) of functional magnetic resonance (fMRI) studies assessing working memory in euthymic bipolar I patients points to abnormal activation patterns in the dorsolateral pre-frontal cortex (DLPFC), ventrolateral prefrontal cortex, other prefrontal regions, as well as the parietal and temporal cortices.…”
Section: Introductionmentioning
confidence: 99%
“…A third theme is abnormal activity in emotion processing circuitry, including amygdala, orbitofrontal cortex and temporal cortex, during non-emotional, cognitive task performance in bipolar disorder(23,24)(Table 1;ST1). For example, studies reported abnormally elevated amygdala activity in adults with bipolar disorder across different mood states during performance of a variety of cognitive tasks(25-27), and increased amygdala activity during motor response inhibition in manic versus remitted adults with bipolar disorder(28).…”
Section: Introductionmentioning
confidence: 99%